2016
DOI: 10.18553/jmcp.2016.22.10.1167
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacy Intervention on Prior Authorization Success and Efficiency at a University Medical Center

Abstract: No outside funding supported this study. The authors report no conflicting interests. Melnikow and Cutler contributed the study concept and design, with assistance from the other authors. Lester, Barca, and She collected the data, and Xin performed all statistical analysis. Cutler was the major contributor to manuscript preparation, with assistance from the other authors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…After incorporating phoned or faxed prescriptions, electronic prescriptions were still associated with a 10% increase in first-fill adherence [24]. An evaluation of a centralized, pharmacist-led prior authorization initiative in a university-based medical center showed that use of the centralized system improved prescription approval rates and significantly reduced time to approval [25].…”
Section: Discussionmentioning
confidence: 99%
“…After incorporating phoned or faxed prescriptions, electronic prescriptions were still associated with a 10% increase in first-fill adherence [24]. An evaluation of a centralized, pharmacist-led prior authorization initiative in a university-based medical center showed that use of the centralized system improved prescription approval rates and significantly reduced time to approval [25].…”
Section: Discussionmentioning
confidence: 99%
“…As key learned intermediaries between prescribers and patients, pharmacists’ opportunities to advance care for virtually any illness include 4 1) assisting prescribers’ improvement in medication selections, doses, routes of administration, and product formulations; 26 2) monitoring of efficacy and adverse effects; 27 3) providing patient education, both about the disease as well as about treatments, including proper use of medications as well as devices; 28 and 4) helping resolve medication access and insurance issues. 29…”
Section: Opportunities For Pharmacists In Cluster Headachementioning
confidence: 99%
“…When patients incur a lapse in coverage or an insurance rejection for their medication, pharmacists and pharmacy technicians can efficiently navigate the process of ensuring medication access and affordability. Pharmacist-led PA processes have been shown to improve approval rates and significantly reduce time to PA approval [46]. High medication access rates have been reported in integrated specialty pharmacy models [33,47].…”
Section: Integrated Health-system Specialty Pharmacist Rolementioning
confidence: 99%